Immunohistochemical localization of irisin in skin, eye, and thyroid and pineal glands of the crested porcupine (Hystrix cristata) - Tarakci, B. Gencer; Girgin, A.; Timurkaan, S.; Yalcin, M. H.; Gur, F. M.; Karan, M. (Taylor & Francis Inc, 2016)
Irisin was first identified in muscle cells. We detected irisin immunoreactivity in various organs of the crested porcupine (Hystrix cristata). In the epidermis, irisin immunoreactivity was localized mainly in stratum basale, stratum spinosum and stratum granulosum layers; immunoreactivity was not observed in the stratum corneum. In the dermis, irisin was found in the external and internal root sheath, cortex and medulla of hair follicles, and in sebaceous glands. Irisin immunoreactivity was found in the neural retina and skeletal muscle fibers associated with the eye. The pineal and thyroid glands also exhibited irisin immunoreactivity.
Keywords: crested; porcupine; eye; immunohistochemistry; irisin; pineal; skin; thyroid